Design method, performance evaluation, and tolerance analysis of the rectilinear cooling channel for a muon collider - Ruihu Zhu; Chris Rogers; Jiancheng Yang; He Zhao; Cheng Guo; Jiangdong Li (Physical Review Accelerators and Beams)
The muon collider has the potential to be a powerful tool for the exploration of frontiers in particle physics. In order to reach high luminosity, the 6D emittance of the muon beam needs to be reduced by several orders of magnitude. The cooling process for a muon collider involves two parts: initial six-dimensional cooling and final transverse cooling. This paper focuses on the former and proposes a conceptual design of the rectilinear cooling channel with additional dipole magnets. We first introduce a general method for designing the rectilinear cooling channel. Subsequently, we apply this method to develop two rectilinear cooling channels before and after a bunch merge system. Furthermore, we investigate the impact on cooling performance of employing π-mode rf cavities and the effect of errors in the magnetic and rf fields.